Dowry at the Crossroads of Cultures: Tradition and Modernity in Islamic Marriage in Indonesia and Malaysia - Riyansyah, Ahmad (Fakultas Syariah dan Hukum, 2025)
This study aims to examine the dynamics of mahar (dower) practices in Islamic marriage in Indonesia and Malaysia by highlighting the intersection between traditional values and modernity. Mahar is an Islamic legal institution designed to protect women's rights; however, in practice, it is often influenced by cultural norms and social pressures. In various communities, dowry is not only seen as a religious obligation but also as a symbol of social status, potentially triggering economic inequality and marriage barriers. This research employs a normative juridical method with a statute approach and qualitative data analysis through the study of classical and contemporary fiqh literature, positive legal regulations in Indonesia and Malaysia, and societal practices. The findings reveal that although the fundamental principles of dowry in Islam emphasize simplicity and justice, its implementation is frequently shaped by social constructs that hinder the original intent of the sharia. In Indonesia, local customs such as those in Lombok and Minangkabau provide distinct nuances, while in Malaysia, Malay traditions and the symbolic value of mahar have also transformed in the modern era. This study concludes that an educational and reinterpretive approach to mahar is necessary to ensure alignment with maqashid sharia. A renewed understanding of mahar practices is essential to maintain its relevance, fairness, and contextuality in contemporary Muslim societies.